Medial canthopexy using mini-screws &/or micro plates for the surgical treatment of post traumatic telecanthus associated with naso-orbito-ethmoidal fractures - Ahmed Mohamed Medra; Essam M. Ashour; Ehab Aly Shehata (Elsevier, 2021)
Background: The normal bony insertion of the medial canthal tendon can be disrupted after trauma, as a result of ablative surgery or as a consequence of subperiosteal detachment during a craniofacial surgical procedure. Medial canthoplasty is required to avoid telecanthus following these events. Several surgical techniques have been described to reattach the tendon to the posterior lacrimal crest. The techniques of transnasal wiring had been used widely to reconstruct medial canthal tendon. However, some surgeons have preferred the use of ipsilateral techniques that include the nylon anchor suture, the stainless-steel screw and/or miniplates. Aim of the study: This study aims to present a technique for Canthopexy and Medial canthal ligament reconstitution secondary to posttraumatic medial canthal degloving injuries using mini-screws and/or microplates to obtain a consistent and definitive reinforcement of the Medial Canthal ligament and its continuity to the postero-superior surface of the medial orbital wall. Materials and methods: The present study enrolled 23 patients with posttraumatic medial telecanthus deformity that had been treated over a 3-year period from July 2016-June 2019. Clinical examination had been scheduled for all patients regarding evaluation of lacrimal system function, medial canthal position in addition to eyelid measurements. Visual impairment and movements of the eye were evaluated by ophthalmological consultation. Irrigation and probing were used for evaluation of the nasolacrimal system. MCT detachment can be determined by Bowstringing test through subcutaneous palpation of the MCT as one stretches the lid laterally.Eyelid evaluation comprised recording measurements of the inter-canthal distance (ICD), the interpupillary distance (IPD) and the palpebral fissure length (PFL). Telecanthus was assessed by recording the distance (in millimetres) measured between the facial midline and the medial canthus of the injured eye that will be compared to the corresponding values of the uninjured eye preoperatively and at all postoperative follow-up intervals. Radiographic assessment was evaluated by axial, coronal and sagittal C.T scans preoperatively and at 1, 3 and 6 months postoperatively. Results: Medial Canthopexy with mini-screws was performed in 15 patients while a Y-shaped micro plate was utilized in 8 patients. The postoperative medial canthal position had been reported to be satisfactory in all patients, showing a considerable improvement compared with the preoperative position. The patients were re-evaluated at 1,3 and 6 months postoperatively demonstrating absence of any evidence of recurrence and with an acceptable cosmetic result, as the medial canthal concavity had been successfully achieved. All patients were satisfied except one that was overcorrected and re-operated for re correction. Another one was under corrected and had undergone revision. However, at 6 weeks postoperatively, one patient had a wound dehiscence resulting in medial canthal detachment and required retreatment. In all patients (except for the one of wound dehiscence), the post-canthopexy Bow String test failed to cause loss of canthal re-attachment and reconstruction or even lateral displacement of the medial canthal tendon throughout all the follow-up intervals. Conclusions: Medial Canthopexy using mini-screws and/or microplates is a simple, easy and reliable technique for the surgical correction of posttraumatic Telecanthus secondary to MCT detachment as this technique promotes satisfactory post-surgical outcomes with resultant acceptable esthetic and functional results.